Coastal Circulation Off Kuala Terengganu - Marghany, Maged Mahmoud (1994)

(untitled)
The aim of this study was to determine the type of the current patterns in the coastal waters o f Kuala Terengganu. This study was divided in two parts. The first part was to determine the pattern of thermohaline circulation . This was done by sampling 25 stations a long the coastal water of Kuala Terengganu.The second part was to measure the subsurface current by ONO- self recording current meter and drogue. The thermohaline circulation was dominated by mixing during the north-east monsoon period ( October 1992, February and March 1993) due to the turbulence resulting from the action o f wind and tide . A dominant feature of this study was the occurrence of upwelling during the south-we st monsoon period ( May to August 1992 ) . The downwelling occurrences are in the north-east monsoon. The study showed that the subsurface current in the coastal waters of Kuala Terengganu were influenced by the tide . The current speed throughout this study varied from 0.012 to 2.6 m/s. The tide throughout this study was diurnal in nature . A dominant feature through this study was tidal current while , the winds have no impact o n the water movement . Finally the data of surface current illustrated that the water meanders in the month of April 1993 . Meander rotated in clockwise direction from the north to south-west direction with an ave rage current speed of about 0.4 m/s.